Methylphenidate is more effective to improve inhibitory control and working memory compared to tDCS in children and adolescents with attention deficit/hyperactivity disorder: a proof-of-concept study - D’Aiello, Barbara; Lazzaro, Giulia; Battisti, Andrea; Pani, Pierpaolo; Di Vara, Silvia; De Rossi, Pietro; Pretelli, Italo; Costanzo, Floriana; Vicari, Stefano; Menghini, Deny (Frontiers in Neuroscience, 2023)
Attention-deficit/hyperactivity disorder (ADHD) is characterized by an inappropriate, pervasive and persistent pattern of inattention, hyperactivity, and/or impulsivity and associated with substantial functional impairment. Despite considerable advances in the understanding and management of ADHD, some patients do not respond well to methylphenidate (MPH), the first-choice pharmacological treatment. Over the past decades, among non-invasive brain stimulation techniques, transcranial direct current stimulation (tDCS) has proven to be an effective and safe technique to improve behavior and cognition in children with neurodevelopmental disorders, including ADHD, by modifying cortical excitability. However, the effect of tDCS has never been directly compared with that of the MPH. The present randomized sham-controlled trial evaluated the effect of a single session of anodal tDCS compared with the administration of a single dose of MPH in children and adolescents with ADHD. After completing baseline assessment (T0), 26 children and adolescents with ADHD were exposed to 3 conditions with a 24-hour interval-sessions: A) a single session of anodal tDCS over the left dorsolateral prefrontal cortex (DLPFC); B) a single session of sham tDCS over the left DLPFC; C) a single dose of MPH. Our results showed that after administering a single dose of MPH, children and adolescents with ADHD improved inhibitory control and visual-spatial WM compared with baseline, anodal, and sham tDCS. However, a single session of active tDCS over the left DLPFC was not effective compared with either baseline or sham tDCS. In conclusion, our protocol in ADHD involving a single tDCS session did not demonstrate consistent improvements in neurocognitive features compared with baseline, sham tDCS, or single MPH administration. Different protocols need to be developed to further test the effectiveness of tDCS in improving ADHD symptoms.